2008
DOI: 10.1192/pb.bp.107.018366
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of crisis resolution/home treatment teams in England: national survey 2005–2006

Abstract: Aims and MethodTo describe implementation of crisis resolution/home treatment (CRHT) teams in England, examine obstacles to implementation and priorities for development. We conducted an online survey followed by a telephone or face-to-face interview among 243 teams.ResultsConsiderable progress has been made in implementation with a subset of teams demonstrating strong fidelity to the Department of Health's guidance, particularly in urban settings. However, only 40% of teams described themselves as fully estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 5 publications
8
62
0
Order By: Relevance
“…We also controlled for the availability of CRHT teams that provide alternative home care in an emergency and play a 'gatekeeping' role in admissions to hospital. 25,54,55 Data on CRHTs were collected as part of the Mental Health Services Mapping Data between 2000 and 2009 at the level of 'local implementation teams' (LITs) which partly cover the geography of local authority social services. 56 There is an almost one-to-one correspondence between LITs and the approximately 150 commissioning organisations in England at that time, primary care trusts (PCTs).…”
Section: Data Sets Used To Generate Other Covariatesmentioning
confidence: 99%
“…We also controlled for the availability of CRHT teams that provide alternative home care in an emergency and play a 'gatekeeping' role in admissions to hospital. 25,54,55 Data on CRHTs were collected as part of the Mental Health Services Mapping Data between 2000 and 2009 at the level of 'local implementation teams' (LITs) which partly cover the geography of local authority social services. 56 There is an almost one-to-one correspondence between LITs and the approximately 150 commissioning organisations in England at that time, primary care trusts (PCTs).…”
Section: Data Sets Used To Generate Other Covariatesmentioning
confidence: 99%
“…It seems that despite these guidelines and the implementations of CRHT, the input people receive from CRHT remains inconsistent as evidenced by the experiences of the people in this study. It seems that some CRHT teams continue to be under resourced in order to provide services that adhere to the model suggested by the DOH, for example providing out of hours support (Onyett, et al, 2008). In view of the nature of these people's difficulties, they need someone to turn to when difficulties arise, particularly at night when they feel most alone as voiced by Marie talking about how desperate she felt at night.…”
Section: Links To Previous Researchmentioning
confidence: 99%
“…A national survey of CRHT in 2006 reported that many were under resourced to meet the demands of out of hours assessments and just over half offered out of hours services and only 8% of teams had a psychologist despite these being national guidelines (Onyett et al, 2008).…”
Section: Crisis Resolution/home Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The principles are spelled out, but the details need to be worked out on a local basis. On a practical level, access to psychotherapy services is limited by a number of factors that include, together with lack of adequate service provision (Centre for Economic Performance's Mental Health Policy Group, 2006), the referral path and the length of waiting lists. There are also reports of increased levels of stress among GPs (Royal College of General Practitioners, 2005), who have to deal in more complex ways with more difficult patients and limited funding.…”
Section: Discussionmentioning
confidence: 99%